Salivary biomarkers and early childhood caries - Degrève, Clémentine Alice Juliette (2017)
Background - Dental caries is the most common chronic childhood disease. Early Childhood Caries is a severe and early form of the carious disease that can compromise child’s oral and systemic health. It is essential to make use of all existing preventive methods to avoid and control this serious disease. The identification of caries salivary biomarkers through salivary chair side tests, has been considered a good strategy to identify risky children in order to implement early preventive ECC programs. Objective: This review will focus on how salivary tests can detect caries related salivary biomarkers, to help identify children at risk of caries development, therefore assisting on ECC prevention strategies. Methods: A bibliographic search was carried out using the keywords: “early childhood caries”, “ salivary factors”, “salivary biomarkers”, “pediatric dentistry”, “caries prevention”. After applying the search limits and the inclusion/exclusion criteria a total of 22 articles were selected for review.